Model E-Asesmen Berbasis Aplikasi pada Sekolah Menengah Atas di Era Digital: Systematic Literature Review - Ashari, Muhammad Khakim; Athoillah, Sukijan; Faizin, Moh (Universitas Islam Sultan Agung, 2023)
Education in today's digital era is required to be adaptive and accommodating to the development of information and communication technology. The education process is carried out dynamically according to civilisation. One of the significant changes that occur today is the transfer of assessment practices from conventional-traditional to electronic assessment practices which are then called E-Assessment. This electronic assessment is developed with various variants, starting from web-based, applications, and so on. Internet access has been massive and widespread throughout the region, making most people assume that E-assessment is relevant to be applied in today's learning world. This research is a type of qualitative research with a systematic literature review (SLR) approach. Data sources come from research journal articles and books that are in accordance with the theme of the discussion. The data analysis technique uses content analysis. The findings or results of the study are that E-assessment is relevant to be implemented in senior high schools because of their skills in accessing and operating various applications. The digital literacy possessed by today's millennial generation greatly supports the E-assessment process in schools. Application-based E-Assessment can be developed with several applications, such as kahoot, quizizz, moodle, and others. The application of E-assessment has several advantages, such as saving money, reducing time for correction, feedback and evaluation results can be received in real time, and improving the digital skills of educators and students